KESETARAAN GENDER DALAM PEMBANGUNAN PERTANIAN - Setiawan, Eko (Jurnal Studi Gender dan Anak, 2024)
The issue of gender equality is mainly reflected in terms of access to opportunities and possibilities, participation in decision-making processes, control of resources and benefits from agricultural development outcomes. Women's traditional rights, including children's rights, are not diminished due to the utilization of agricultural natural resources and their products. Equality of access of women and men to information on the use of capital, agricultural facilities and infrastructure must also continue to be fought. The purpose of writing this article is to analyze the concept of gender in wages and the division of agricultural labor and the role of women in agricultural development. Using literature study research, in the form of a series of activities related to library data collection methods, reading and recording, and managing research materials. Data collection comes from textbooks, national and international online journals, scientific articles, literature reviews containing the concept of gender in agricultural development. The results showed that development in agriculture, the role of women tends to be less meaningful and gender inequality occurs. This also applies to agriculture, where women are given "feminine" work that requires accuracy, patience and is not too heavy. Keywords: Gender Equality, Development, Agriculture Abstrak Isu kesetaraan gender terutama tercermin dalam hal akses terhadap peluang dan kemungkinan, partisipasi dalam proses pengambilan keputusan, penguasaan sumber daya dan manfaat dari hasil pembangunan pertanian. Hak-hak tradisional perempuan, termasuk hak anak-anak, tidak berkurang karena pemanfaatan sumber daya alam pertanian dan produk-produknya. Kesetaraan akses perempuan dan laki-laki terhadap informasi penggunaan modal, sarana dan prasarana pertanian juga harus terus diperjuangkan. Tujuan penulisan artikel ini adalah untuk menganalisis konsep gender dalam pengupahan dan pembagian kerja pertanian dan peran perempuan dalam pembangunan pertanian. Menggunakan penelitian studi kepustakaan, berupa serangkaian kegiatan yang berkenaan dengan metode pengumpulan data pustaka, membaca dan mencatat, serta mengelola bahan penelitian. Pengumpulan data berasal dari textbook, jurnal online nasional dan internasional, artikel ilmiah, literature review yang berisikan tentang konsep gender dalam pembangunan pertanian. Hasil penelitian menunjukkan pembangunan dalam bidang pertanian, peran perempuan cenderung kurang berarti dan terjadi ketidaksetaraan gender. Hal ini juga berlaku pula di pertanian, dimana perempuan diberi jatah pekerjaan yang bersifat feminim yang membutuhkan ketelitian, kesabaran dan tidak terlalu berat. Kata Kunci: Kesetaraan Gender, Pembangunan, Pertanian